2020
DOI: 10.1530/ec-20-0209
|View full text |Cite
|
Sign up to set email alerts
|

Platelet parameters in Chinese older adults with metabolic syndrome

Abstract: Purpose: We aimed to examine the associations of platelet parameters with the presence of metabolic syndrome in community-dwelling older Chinese adults. Methods: Study sample was from the Weitang Geriatric Diseases Study, which included 4338 individuals aged 60 years or above. The mean age of the participants was 68 years. Metabolic syndrome was defined based on the Adult Treatment Panel Ⅲ criteria. Platelet parameters were assessed using an automated hematology analyzer. Multiple log… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…In addition, some studies did not find that having MetS was associated with a significant difference in MPV values. [ 10 , 22 , 38 , 39 ] These differences across studies may be explained in part by several factors such as the selection criteria (i.e., general population or diabetic patients), diagnostic criteria for MetS, race, and age (i.e., pre-pubertal children or older adults), thus suggesting that the association between MPV and MetS deserves further scrutiny.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some studies did not find that having MetS was associated with a significant difference in MPV values. [ 10 , 22 , 38 , 39 ] These differences across studies may be explained in part by several factors such as the selection criteria (i.e., general population or diabetic patients), diagnostic criteria for MetS, race, and age (i.e., pre-pubertal children or older adults), thus suggesting that the association between MPV and MetS deserves further scrutiny.…”
Section: Discussionmentioning
confidence: 99%
“…40 In this sense, 83.6% of the patients with diabetes from our cohort received specific anti-diabetic treatment, at least partially explaining the lower MPV levels that we found when compared to other obese individuals without DM. In relation to MS, several authors reported a nonsignificant association between MS and MPV, 39,41 but one of these studies found that some components of MS were associated with a higher MPV. 39 However, Park et al found that the MPV was significantly decreased in a cohort of Korean women suffering from MS, 42 and other authors have also reported similar results.…”
Section: Discussionmentioning
confidence: 99%
“…Hematological markers are thought to be related to IR, which is regarded to be a key component of MetS [ 25 ]. Insulin resistance-induced vascular dysfunction may lead to a decreased production of prostacyclin and nitric oxide by the vascular endothelium, which would promote an increase in platelet activity and a subsequent production of more platelets [ 24 ]. Endothelial dysfunction in MetS is also linked to elevated leukocyte count by enhancing leukocyte differentiation [ 26 ].…”
Section: Introductionmentioning
confidence: 99%